Implementation of Staffing and Directing Strategies - Sugiharti, Sugiharti (CV. ULIL ALBAB CORP, 2024)
Strategy formulation often fails to consider the value of individual skills and capabilities to the success of the strategy. In fact, the high competitive value that can help a company to win the competition lies in its human resources. If a company wants to implement a new strategy, it has to change its human resource management strategy significantly, especially in terms of staffing. Putting the right people in the right positions, matching individual skills with the task of implementing the strategy, including developing human resources to be able to adapt to the specifications they should have. This research aims to explain how strategy can be implemented and how actions can be organised to implement the company's strategy well. The method used in this research is descriptive analysis, which involves collecting data from various sources and then analysing the data.